2022
DOI: 10.35833/mpce.2021.000220
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Stability Constrained Optimal Power Flow for Unbalanced Distribution System Based on Semidefinite Programming

Abstract: This paper proposes a voltage stability constrained optimal power flow (VSC-OPF) for an unbalanced distribution system with distributed generators (DGs) based on semidefinite programming (SDP). The AC optimal power flow (ACOPF) for unbalanced distribution systems is formulated as a chordal relaxation-based SDP model. The minimal singular value (MSV) of the power flow Jacobian matrix is adopted to indicate the voltage stability margin. The Jacobian matrix can be explicitly expressed by ACOPF state variables. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, second-order cone programming (SOCP) facilitates effective solutions for problems involving linear and quadratic constraints [30]. New studies, like [31], look into semidefinite programming (SDP), and the work in [32] uses convexification techniques. Likewise, exponential programming (EXP), which models NOPT objectives and constraints through exponential functions [33].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, second-order cone programming (SOCP) facilitates effective solutions for problems involving linear and quadratic constraints [30]. New studies, like [31], look into semidefinite programming (SDP), and the work in [32] uses convexification techniques. Likewise, exponential programming (EXP), which models NOPT objectives and constraints through exponential functions [33].…”
Section: Related Workmentioning
confidence: 99%
“…Yet, these classical methods face challenges such as scalability, computation time, convergence, and practical precision, underscoring their inherent complexity and limitations. Furthermore, the use of relaxations or approximations affects the optimization accuracy [35].…”
Section: Related Workmentioning
confidence: 99%
“…O NE of the distinctive features of modern power systems is the growing penetration of renewable energy sources into power systems, which has the notable impacts on the secure and stable operation of power systems [1]. It has been reported that power systems tend to operate near the stability boundary due to the increasing load demand and the intense uncertainty driven by the volatility and randomness of renewable energy sources [2], [3]. Coupled with that comes from loads, the uncertainties from both renewable energy sources and loads increase the complexities of the analysis and control of power systems.…”
Section: Introductionmentioning
confidence: 99%
“…Her iki durumda da, güç sistemlerinde gerilim kararlılığı problemi ortaya çıkabilmektedir. Güç sistemlerinde gerilim kararlılığı, bara gerilim değerlerinin tüm koşullar altında (herhangi bir bozucu etki olması durumunda bile) belirlenen sınır değerleri arasında kalabilmesi olarak ifade edilmektedir [2].…”
Section: Giriş (Introduction)unclassified